2011
DOI: 10.1507/endocrj.k10e-330
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight loss and treatment with metformin on serum vaspin levels in women with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is one of the commonest endocrine disorders in women of reproductive age, affecting 5-10% of them, and the leading cause of anovulatory infertility in developed countries [1,2]. The most frequent signs of PCOS are irregular menstruation, due to oligo-or anovulation, as well as signs of androgen excess, including hirsutism, oily skin, acne and androgenic alopecia [3].Patients with PCOS frequently have insulin resistance, pancreatic β-cell dysfunction, glucose intolerance, type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 40 publications
3
40
1
Order By: Relevance
“…There is a controversy between our results, where no significant changes of vaspin plasma levels in nonobese PCOS women was observed and other studies which showed increased vaspin plasma levels in PCOS women [12,18,19] [18] study might represent a compensatory mechanism to preserve insulin sensitivity and glucose tolerance which are impaired in obesity.…”
Section: Discussioncontrasting
confidence: 86%
“…There is a controversy between our results, where no significant changes of vaspin plasma levels in nonobese PCOS women was observed and other studies which showed increased vaspin plasma levels in PCOS women [12,18,19] [18] study might represent a compensatory mechanism to preserve insulin sensitivity and glucose tolerance which are impaired in obesity.…”
Section: Discussioncontrasting
confidence: 86%
“…Positive associations with HOMA-IR and glucose were found, suggesting that high vaspin levels may be a consequence of insulin resistance. Similar results were found by Koiou et al [38]. In their study, serum vaspin levels were higher in both lean and obese PCOS patients than in controls.…”
Section: New Markers: Structure Action and Role In Insulin Resistancesupporting
confidence: 91%
“…Several pediatric studies, but not all, illustrated possible relationships between vaspin, insulin sensitivity, and obesity [13,20,21]. Some reported that weight reduction decreased circulating vaspin levels [22][23][24], but others did not [13,25].…”
Section: Discussionmentioning
confidence: 99%